2015
DOI: 10.1080/10412905.2015.1037021
|View full text |Cite
|
Sign up to set email alerts
|

Scents from Brazilian Cerrado: chemical composition of the essential oil fromPseudobrickellia brasiliensis(Asteraceae)

Abstract: The chemical composition of the essential oil from the leaves of Pseudobrickellia brasiliensis (Asteraceae) from the Brazilian Cerrado was analyzed by GC/FID and GC/MS. Thirty-four out of thirty-eight components detected were identified. Major compounds in the oil were terpinen-4-ol (38.6%), γ-terpinene (19.5%), α-terpinene (7.8%) and α-terpineol (4.5%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Previous studies with P. brasiliensis apolar extracts revealed the presence of triterpenes and sesquiterpenes, such as hidroxigermacreno, lupeol, β-amyrin acetate, spathulenol, cadinene, cadinol, oplopanona acetate, and α-acetoxy-β-amyrin ( 20 ). Moreover, the essential oil from the leaves contains the major compounds terpinen-4-ol, γ-terpinene, α-terpinene, and α-terpineol ( 21 ). However, no study has been conducted to identify the chemical compounds present in the polar extract of P. brasiliensis , a similar formulation used in folk medicine.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies with P. brasiliensis apolar extracts revealed the presence of triterpenes and sesquiterpenes, such as hidroxigermacreno, lupeol, β-amyrin acetate, spathulenol, cadinene, cadinol, oplopanona acetate, and α-acetoxy-β-amyrin ( 20 ). Moreover, the essential oil from the leaves contains the major compounds terpinen-4-ol, γ-terpinene, α-terpinene, and α-terpineol ( 21 ). However, no study has been conducted to identify the chemical compounds present in the polar extract of P. brasiliensis , a similar formulation used in folk medicine.…”
Section: Resultsmentioning
confidence: 99%
“…This is the first time that the presence of kaurenoic acid in P. brasiliensis has been reported. There are studies that indicate some activities for kaurenoic acid and derivatives: anticonvulsant, anticancer, anti-inflammatory, and others (Okoye et al, 2013;Lima Silva et al, 2015;Simão et al, 2016). Chemotaxonomic studies have indicated the presence of terpenes in the Asteraceae family, and diterpenes with a kaurane skeleton was found in the Eupatorieae tribe (Alvarenga et al, 2005).…”
Section: Chemical Constituents In the Hexane And Ethyl Acetate Extractsmentioning
confidence: 99%
“…The whole plant or parts of the plant are popularly used as an analgesic and an antiinflammatory and topical wound healer in a tanned or macerated form in alcohol (Ribeiro et al, 2001;Silva et al, 2015).…”
Section: Introductionmentioning
confidence: 99%